2010
DOI: 10.2134/agronj2010.0011
|View full text |Cite
|
Sign up to set email alerts
|

Grain Corn and Soil Nitrogen Responses to Sidedress Nitrogen Sources and Applications

Abstract: Th e effi ciency of synthetic N fertilization can be improved by selecting the fertilizer source and application that best matches the soil N supply and crop demand. A fi eld experiment was conducted for 3 yr (2004-2006) on a clay soil near Québec City, QC, Canada, to evaluate the eff ects of N fertilizer source and application on corn (Zea mays L.) yield, plant N accumulation, and residual soil inorganic N. Treatments consisted of an unfertilized control (0 N) and three sources of N fertilizer (urea ammonium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
36
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
16
36
0
3
Order By: Relevance
“…It was consistent with other studies (Halvorson et al, 2005;Gagnon and Ziadi, 2010). Halvorson et al (2005) reported a significant increase in grain yields with rates up to 224 kg N ha -1 under irrigated conditions.…”
Section: Discussionsupporting
confidence: 92%
“…It was consistent with other studies (Halvorson et al, 2005;Gagnon and Ziadi, 2010). Halvorson et al (2005) reported a significant increase in grain yields with rates up to 224 kg N ha -1 under irrigated conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The direct effect of N addition was related to osmotic potential and ion concentration that inhibit microbial growth (Treseder 2008). In our field study, mean in-season soil mineral N content was higher with UAN and CAN than with AA (Gagnon and Ziadi 2010). The lower depressive effect of NH 4 source could also result from the conversion mechanisms of assimilation and dissimilation of the solubilized organic C with ammonia by the microbial processes (Norman et al 1988).…”
Section: Discussionmentioning
confidence: 59%
“…The second period (Period 2) began at sidedress N application and ended when soil mineral N content in N treatments reached levels similar to the control soils, corresponding During each growing season, soil samples were taken at specific times after sidedress N application from the 0 to 15 cm layer with a 2.5 cm diameter soil probe according to a systematic spatial collecting pattern due to band application. Soil extractable NO 3 -N and NH 4 -N were reported in Gagnon and Ziadi (2010) and WEOC in Gagnon et al (2011). Soil pH was determined with a soil to water ratio of 1:2 (Hendershot et al 2008).…”
Section: Field Experimentsmentioning
confidence: 99%
“…L'apport d'azote (N) mine´ral ou organique permet ge´ne´ralement d'augmenter les rendements du ble ( Ayoub et al 1994;Tran et Tremblay 2000;Ziadi et al 2008), du maı¨s-grain (Tran et al 1997;Elmi et al 2002;Ma et al 2005;Tremblay et al 2007; Gagnon et Ziadi 2010), mais n'a pas beaucoup d'impact sur les rendements du soya (Tremblay et Beausoleil 2000;Pellerin et al 2006). Plusieurs facteurs peuvent influencer les besoins en e´le´ments fertilisants d'une culture : la disponibilite´de l'e´le´ment fertilisant dans le sol, la localisation ge´ographique, les conditions climatiques, les types de sol, les rotations, les cultivars ou les hybrides, etc.…”
unclassified
“…Plusieurs facteurs peuvent influencer les besoins en e´le´ments fertilisants d'une culture : la disponibilite´de l'e´le´ment fertilisant dans le sol, la localisation ge´ographique, les conditions climatiques, les types de sol, les rotations, les cultivars ou les hybrides, etc. Chantigny et al 2008;Ziadi et al 2008;Gagnon et Ziadi 2010). Au Que´bec, il est recommande´d'apporter de 90 a`120 kg N ha…”
unclassified